Pronunciation Assessment: Relating theCEFR’s Phonological Control Scale toIntelligibility and Comprehensibility Measures (Revista de Estudos da Linguagem, 2025)
Research in pronunciation learning and teaching over the past years has advanced the idea that working with the intelligibility and comprehensibility constructs is fundamental to developing pronunciation for successful communication. This study investigates the relationship between the Common European Framework of Reference for Languages - CEFR phonological scale (2018 version), and two measures commonly used in second language (L2) speech research, namely, intelligibility and comprehensibility rates. Speech samples from 16 Brazilian speakers of English were collected. Their speech samples were assessed by 14 listeners, teachers of English, in terms of intelligibility, comprehensibility and phonological control. The raters transcribed the speech samples, which generated an intelligibility score (number of words correctly transcribed); for comprehensibility, the raters assigned a level of difficulty in understanding the speech through a nine-point scale; finally, they used the CEFR scale to rate the level of phonological control for each speaker. Results show a highly significant correlation between intelligibility and comprehensibility, but not significant correlation between these two speech dimension variables and phonological control.